Identification and expression profiling of Pht1 phosphate transporters in wheat in controlled environments and in the field - Grün, A.; Buchner, P.; Broadley, M.R.; Hawkesford, M.J. (Wiley, 2018)
Phosphorus (P) is an important macronutrient with critical functions in plants. Phosphate (Pi) transporters which mediate Pi acquisition and Pi translocation within the plant are key factors in Pi deficiency responses. However, their relevance for adaptation to long-term Pi limitation under agronomic conditions, particularly in wheat, remains unknown.